Enjoying the Quiet Life under Deregulation? Evidence from Adjusted Lerner Indices for U.S. Banks - Koetter, Michael; Kolari, James W.; Spierdijk, Laura (The Review of Economics and Statistics, 2012)
The quiet life hypothesis posits that firms with market power incur inefficiencies rather than reap monopolistic rents. We propose a simple adjustment to Lerner indices to account for the possibility of forgone rents to test this hypothesis. For a large sample of U.S. commercial banks, we find that adjusted Lerner indices are significantly larger than conventional Lerner indices and trending upward over time. Instrumental variable regressions reject the quiet life hypothesis for cost inefficiencies. However, Lerner indices adjusted for profit inefficiencies reveal a quiet life among U.S. banks.